The Inhibitor Activity Test of Green Okra Fruit Fraction (Abelmoschus Esculentus) Against Candida Albicans - Christina Astutiningsih; Jesi Kristianti (Science Midwifery, 2022)
This study was done to analyze the inhibitory activity of green Okra Fruit fraction against Candida albicans. The green Okra fruit is originated from Cepiring, Kendal. Green Okra fruit is a vegetable that contains compounds including flavonoids, alkaloids, tannins, steroid, triterpenoids stapling that are able to provide antifungal activity. The green Okra fruit was remacerated with ethanol 80 % followed fractination with n-hexane, diethyl ether, and ethyl acetate . The n-hexane, diethyl eter and ethyl acetate Okra fruit can inhibitory activity against Candida albicans. The test method for inhibitory activity was the disc method using DMSO as a negative blank and Nystatin as a positive blank. The results obtained Okra Fruit fraction can be used as an antifungi Candida albicans and diameter zona of fraction n-hexane, diethyl eter and ethyl acetate were 15,09; 17.11, and 20,28 mm The conclusion of this study is the concentration of the fraction were directly proportional to its inhibitory power, and there weredifferences in and there were differences in antifungal activity. The active campounds contained in the diethyl eter and ethyl acetate fractions of okra fruit was positive for flavonoids, alkaloids, saponins, terpenoids and tannnis, while the n-hexane fraction contained saponins, terpenoids and tannins.